2013
DOI: 10.1111/1462-2920.12023
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term monitoring of the human intestinal microbiota composition

Abstract: The microbiota that colonizes the human intestinal tract is complex and its structure is specific for each of us. In this study we expand the knowledge about the stability of the subject-specific microbiota and show that this ecosystem is stable in short-term intervals (< 1 year) but also during long periods of time (> 10 years). The faecal microbiota composition of five unrelated and healthy subjects was analysed using a comprehensive and highly reproducible phylogenetic microarray, the HITChip. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
156
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(177 citation statements)
references
References 66 publications
(97 reference statements)
15
156
1
5
Order By: Relevance
“…However, the microbiota similarities, both in short and long term, were still remarkably lower than previously observed for western adults by using the same microarray technique for microbiota assessment (JalankaTuovinen et al, 2011;Rajilić-Stojanović et al, 2013;Fuentes et al, 2014;Satokari et al, 2014). Furthermore, we found that the most predominant Figure 6 The development of core microbiota # .…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, the microbiota similarities, both in short and long term, were still remarkably lower than previously observed for western adults by using the same microarray technique for microbiota assessment (JalankaTuovinen et al, 2011;Rajilić-Stojanović et al, 2013;Fuentes et al, 2014;Satokari et al, 2014). Furthermore, we found that the most predominant Figure 6 The development of core microbiota # .…”
Section: Discussionmentioning
confidence: 49%
“…In contrast, the gut microbiota of healthy adults is individual specific and relatively stable in time (Claesson et al, 2011;Jalanka-Tuovinen et al, 2011;Rajilić-Stojanović et al, 2013). Two main phyla, Firmicutes and Bacteroidetes, constitute over 90% of the microbiota in healthy adults, followed by Actinobacteria, Proteobacteria and Verrucomicrobia (Claesson et al, 2011;Jalanka-Tuovinen et al, 2011;RingelKulka et al, 2013;Voreades et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While there is some debate on the discrete and permanent nature of enterotypes within the human literature (Arumugam et al, 2011;Wu et al, 2011;Huse et al, 2012;Rajilić-Stojanović et al, 2013), our functional predictions of metagenome content suggest that differing community types in the guppy system have inherent functional differences. For instance, guppies categorized to enterotype 1 were estimated to have the greatest relative proportion of their metagenomes devoted to vitamin biosynthesis.…”
Section: The Functional Implications Of Variable Gut Communitiesmentioning
confidence: 75%
“…The complexity of the intestinal microbial communities requires the application of highthroughput techniques, including metagenomics and 16S rRNA-based approaches. The microbiota composition fluctuates around a stable individual core, and the homoeostasis of this intestinal ecosystem has been shown to be a key factor in the maintenance of health and development of disease (Jalanka-Tuovinen et al, 2011;Rajilic-Stojanovic et al, 2012;Faith et al, 2013). Recently, a metagenomics analysis of European subjects showed that the intestinal microbiota of individuals can be assigned to one of three groups, named enterotypes, based on composition and relative abundance of certain key bacterial groups (Arumugam et al, 2011), which can fluctuate over time (Wu et al, 2011;Rajilic-Stojanovic et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The microbiota composition fluctuates around a stable individual core, and the homoeostasis of this intestinal ecosystem has been shown to be a key factor in the maintenance of health and development of disease (Jalanka-Tuovinen et al, 2011;Rajilic-Stojanovic et al, 2012;Faith et al, 2013). Recently, a metagenomics analysis of European subjects showed that the intestinal microbiota of individuals can be assigned to one of three groups, named enterotypes, based on composition and relative abundance of certain key bacterial groups (Arumugam et al, 2011), which can fluctuate over time (Wu et al, 2011;Rajilic-Stojanovic et al, 2012). Currently, however, this concept is under extensive debate, where researchers rather favour a continuous gradient as opposed to separate enterotypes (Huse et al, 2012;Jeffery et al, 2012;Yong, 2012).…”
Section: Introductionmentioning
confidence: 99%